New Procedures for Catalytic Carbophilic Activation by Gold and Gallium π-Acids - Bour, Christophe; Gandon, Vincent (Synlett, 2015)
Cationic gold(I) complexes are soft Lewis acids that are able to trigger numerous types of nucleophilic attack onto alkenes, allenes, and alkynes (π-acid catalysis). In this account, we initially summarize the novel methods that we have developed to generate such catalysts by silver-free activation of ligated gold(I) chlorides. The advantages of this approach are the use of lower quantities of gold and the ability to scale-up transformations during which the standard gold/silver catalytic system is rapidly decomposed. In the second part, the synthesis and catalytic activity of original organogallium compounds is described. We have shown that (NHC)GaCl2+-type complexes display a high affinity for alkenes and alkynes, and trigger tandem C–C/C–C or C–C/C–H bond formation processes. Thus, they also behave as π-acids. Practical applications of these different gold- and gallium-based catalytic systems for the synthesis of cyclic compounds are presented.1 Introduction2 Silver-Free Two-Component Approaches in Gold Catalysis2.1 The Gold/Copper Catalytic System2.2 Other Applications with Gold/Lewis Acid Systems3 Gallium Catalysis3.1 Cationic Gallium Complexes Supported by N-Heterocyclic Carbene Ligands3.2 Catalytic Applications4 Conclusions
Keywords: gold; gallium; copper; homogeneous catalysis; N-heterocyclic carbenes